2008
DOI: 10.1111/j.1462-2920.2008.01585.x
|View full text |Cite
|
Sign up to set email alerts
|

The NprA nitroreductase required for 2,4‐dinitrophenol reduction in Rhodobacter capsulatus is a dihydropteridine reductase

Abstract: The Rhodobacter capsulatus nprA gene codes for a putative nitroreductase. A recombinant His(6)-NprA protein was overproduced in Escherichia coli and purified by affinity chromatography. This protein contained FMN and showed nitroreductase activity with a wide range of nitroaromatic compounds, such as 2-nitrophenol, 2,4-dinitrophenol, 2,6-dinitrophenol, 2,4,6-trinitrophenol (picric acid), 2,4-dinitrobenzoate and 2,4-dinitrotoluene, and with the nitrofuran derivatives nitrofurazone and furazolidone. NADPH was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…of possibilities to be considered (5,39). Recent data suggest a role as a dihydropteridine reductase for the NR homologue of Rhodobacter capsulatus (40). Structural explanations for the broad substrate repertoires of NR homologues have been discussed (4,41).…”
Section: Tablementioning
confidence: 99%
“…of possibilities to be considered (5,39). Recent data suggest a role as a dihydropteridine reductase for the NR homologue of Rhodobacter capsulatus (40). Structural explanations for the broad substrate repertoires of NR homologues have been discussed (4,41).…”
Section: Tablementioning
confidence: 99%
“…However, the physiological roles of nitroreductases as lipoamide dehydrogenase or dihydropteridine reductase have not yet been demonstrated. We have recently found that the purified NprA nitroreductase from R. capsulatus shows dihydropteridine reductase activity in vitro (Pérez‐Reinado et al , 2008).…”
Section: Bacterial Nitroreductasesmentioning
confidence: 99%
“…In addition to the conversion of inorganic nitrogen molecules discussed above, many bacteria are capable to transform recalcitrant organic nitrogen compounds under various environmental conditions. In this issue one such an example, the conversion of 2,4‐dinitrophenol by Rhodobacter capsulatus , is presented (Pérez‐Reinado et al ., 2008). In this study the npr A gene, encoding for a putative nitroreductase, was heterologously expressed in E. coli and shown to catalyse the reduction a number of nitroaromatic compounds using NADPH as electron donor.…”
Section: Degradation Of Recalcitrant Organic Nitrogen Compoundsmentioning
confidence: 99%